PENERAPAN ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN DI ERA REVOLUSI INDUSTRI 4.0 - Maola, Putri Sofiatul; Karai Handak, Indira Syifa; Herlambang, Yusuf Tri (Universitas Hamzanwadi, 2024)
AbstractArtificial Intelligence (AI) is a contemporary term stemming from the Fourth Industrial Revolution, representing human-created intelligence. Its implementation spans various sectors, including education, as the evolving digital era necessitates such technology to enhance the educational process. The aim is to explore the application of AI in relation to education. The research methodology employed is a literature review. The integration of AI in the realm of education significantly influences learning, particularly in terms of instructional methods. This greatly facilitates both teachers and students in adapting to the teaching and learning activities. Teachers find ease in administrative tasks and student assessments. In the era of the Fourth Industrial Revolution, students are expected to be technologically literate. AI employs systems that assist and enable activities to align with individual abilities and learning styles. However, it's important to note that AI's usage sometimes comes with negative impacts. As a generation in the Fourth Industrial Revolution, it is crucial for us to utilize AI wisely and positively, considering its potential drawbacks.Keywords: Artificial Intelligence, Industrial Revolution 4.0, Education AbstrakArtificial Intelligence (AI) merupakan istilah baru dari Revolusi Industri 4.0 sebagai kecerdasan buatan manusia. Penerapan AI tentunya banyak digunakan di beberapa sektor, termasuk di bidang pendidikan. Pendidikan yang berkembang ke era digital memerlukan teknologi semacam ini untuk membantu meningkatkan pendidikan. Tujuannya untuk mengetahui penerapan AI dalam kaitannya dengan pendidikan. Sedangkan metode penelitian yang digunakan menggunakan metode studi kepustakaan. Penerapan AI dalam dunia pendidikan sangat berpengaruh khususnya dalam hal pembelajaran. Hal ini tentunya sangat memudahkan guru dan siswa dalam menyesuaikan diri dengan kegiatan belajar mengajar. Manfaat yang diperoleh guru adalah mempermudah dalam hal administrasi dan penilaian siswa. Dengan adanya revolusi industri 4.0, pelajar dituntut untuk mampu melek teknologi. AI tersebut menggunakan sistem yang membantu dan memungkinkan dilakukannya kegiatan sesuai dengan kemampuan dan gaya belajarnya. Namun terkadang AI juga mempunyai tantangan dalam penggunaannya, sehingga kita sebagai generasi revolusi industri 4.0 perlu memanfaatkannya secara bijak dan positif dengan memaksimalkan kekuatan yang kita miliki.Kata kunci: Kecerdasan Buatan, Revolusi Industri 4.0, Pendidikan